Influence of Aging on HbA1C: A Cross-Sectional Study on Diabetic Population Attending a Tertiery Care Center of Central Nepal - Adak, Manoranjan; Upadhyay, Hari Prasad (Journal of College of Medical Sciences-Nepal, 2022)
Background: Diabetes mellitus is increasing day by day throughout the globe. So, early diagnosis of diabetes is crucially important in reduction of the complications. This study was conducted to determine the correlation between glucose monitoring by fasting blood glucose and two hours postprandial blood glucose with glycated hemoglobin (HbA1c) in diabetic patients and evaluate whether glycohemoglobin levels increase with age in both sexes Methods: A hospital-based analytical cross-sectional study was carried out from March 2020 to December 2021 in diabetic patients attending at outpatient department (OPD) of College of Medical College and Teaching Hospital, Bharatpur, Chitwan. The total number patients was 696 people. HbA1c, fasting blood sugar (FBS) and postprandial blood sugar (PPBS) were analyzed. Results: Both postprandial blood glucose and fasting blood glucose significantly correlated with HbA1c. Postprandial blood glucose showed better correlation to HbA1c than fasting blood glucose (r = 0.630, P <0.001 vs. r =0.452, P = 0.05). Conclusions: These results show that postprandial blood glucose correlated better than fasting blood glucose to HbA1c. Thus, postprandial blood glucose predicted overall glycemic control better than fasting blood glucose. Based on our study, we may concluded a significant correlation exist between age and HbA1c in Nepalese population.